About the theory of relativity - V. Y. Stetsenko (Литьë и металлургия, 2023)
It is shown that the Earth, the Sun and the stars are not inertial systems. The speed of movement of one inertial system relative to another does not affect the parameters of the moving system. Photons, electrons, protons, neutrons move in space in helical spirals. The equations of the special theory of relativity are not applicable to particles that have particle‑wave properties. It is shown that the fifth coordinate is needed for the curvature of the four‑dimensional space of general relativity. Therefore, gravity cannot be interpreted from the position of the curvature of a four‑dimensional space in a four‑dimensional space. In non‑inertial systems, the forces of inertia are not equivalent to the forces of gravity. Photons moving in space in helical spirals with huge rotational frequencies are stabilized in the direction of rectilinear motion. The gravitational field does not affect the energy of photons and the trajectory of their rectilinear motion. The deviation of the trajectory of stellar photons near the Sun is due to the effect of the atmospheric lens of the Sun. The atmospheres of stars absorb photon energy, which is recorded as a red shift in the radiation spectrum. The displacement of the perihelion of Mercury occurs due to the precession of the axis of Mercury’s orbit under the influence of the gravitational forces of the Sun.